2018
DOI: 10.3892/etm.2018.7095
|View full text |Cite
|
Sign up to set email alerts
|

Hub genes and gene functions associated with postmenopausal osteoporosis predicted by an integrated method

Abstract: Postmenopausal osteoporosis (PO) imposes great burden on individuals and society. This study predicted hub genes and gene functions for PO by an integration of the convergent evidence (CE) method, rank product (RP) algorithm and the combing of P-values. Using the gene expression data, genes were ranked by the CE method, RP algorithm and combing P-values, respectively. Subsequently, the top 100 genes were selected from each of the three gene lists, and then the common genes for two or three methods were denoted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…By constructing mRNA-miRNA-lncRNA networks, this study found that lncRNA XR_003029469.1 had a higher degree in up-regulated lncRNAs network and In ceRNA networks, nodes with high connectivity often have important biological significance, and these genes are called hub genes. 33,34 In most studies, [35][36][37] hub genes were focused on some cancers and diseases such as prostate cancer, large B-Cell lymphoma and non-small cell lung cancer. However, hub genes predicted based on bioinformatics technology may be caused by errors in algorithms or association networks and the function of these genes is not clear and requires further research.…”
Section: Discussionmentioning
confidence: 99%
“…By constructing mRNA-miRNA-lncRNA networks, this study found that lncRNA XR_003029469.1 had a higher degree in up-regulated lncRNAs network and In ceRNA networks, nodes with high connectivity often have important biological significance, and these genes are called hub genes. 33,34 In most studies, [35][36][37] hub genes were focused on some cancers and diseases such as prostate cancer, large B-Cell lymphoma and non-small cell lung cancer. However, hub genes predicted based on bioinformatics technology may be caused by errors in algorithms or association networks and the function of these genes is not clear and requires further research.…”
Section: Discussionmentioning
confidence: 99%
“…Hub genes are highly connected proteins in the PPI network that can play a significant role in identifying the potential therapeutic biomarker [ 31 ]. The three most popular and effective algorithms, including Degree [ 32 ], Maximal Clique Centrality (MCC) [ 33 ], and Maximum Neighborhood Component (MNC) [ 34 ] were used to identify the significant genes from the PPI network through the cytoHubba plugin tool of Cytoscape.…”
Section: Methodsmentioning
confidence: 99%
“…Hub genes are a highly connected protein in the PPI network that can play a significant role to identify the potential therapeutic biomarker [31]. The three most popular and effective algorithms including Degree [32], Maximal Clique Centrality (MCC) [33], Maximum Neighborhood Component (MNC) [34] have been used to identify the significant genes from the PPI network by the cyto-Hubba plugin tool of Cytoscape.…”
Section: Hub Genes Identification and Analysismentioning
confidence: 99%